Methods and Techniques Specific to Human Resource Management - Ovidiu NICOLESCU (Revista de Management Comparat International)
The first part of the study presents the contextual and conceptual novelty elements concerning human resources on which this human resource management approach relies. The conceptual novelty element is represented by the comprehensive approach of human resource management (MRU), focused on the relationships of the organisation with internal and external human stakeholders, not limiting to the traditional approach, managers subordonees. The second part of the paper makes a selection of methods and techniques used in human resource management, grouped on the 14 activities specific to MRU. This ensures a coherent and effective methodological basis for human resource managers and specialists, in agreement with the challenges of the current period of transition to knowledge-based economy. The last part of the study indicates the methods and the techniques recommended to be used in particular during the eight stages of human resource reengineering.